3D Hierarchical Gallium Oxynitride Nanostructures Decorated with Ag Nanoparticles Applied as Recyclable Substrates for Ultrasensitive SERS Sensing. Issue 16 (19th June 2019) - Liu, Qingyun; Chen, Ping; Ye, Yongqin; Wan, Ying; Wang, Bin; Luo, Zhiqiang
Abstract: Developing plasmon‐assisted semiconductor nanocomposites as multifunctional surface‐enhanced Raman scattering (SERS) substrate for detection as well as photodegradation of toxic organic pollutants appears to be a crucial step in upgrading the SERS technique to a quantitative analytical level. However, conventional photocatalytic semiconductor scaffolds are confined in ultraviolet‐light‐active metal oxide nanostructures (TiO2, ZnO, etc.). Herein, the scope of semiconductor scaffold is expanded to visible‐light‐active oxynitrides by developing a robust and ultrasensitive recyclable SERS substrate based on 3D hierarchical gallium oxynitrides (GaON) nanosheets loading with Ag nanoparticles (Ag NPs). Significantly, the bandgap of GaON nanosheets shrinks to 2.9 eV to enable visible‐light adsorption. The as‐fabricated SERS substrate shows a high sensitivity with enhancement factor of 5.2 × 10 7 in R6G detection, and yields a wide detection range of 1.0 × 10 −6 –1.0 × 10 −12 mol L −1 . Assisted with the enhanced charge transfer by generating the Schottky contact at the metal/semiconductor interface and the electron traps played by the residue oxygen, the Ag/GaON nanocomposites show attractive recyclability at visible‐light irradiation with well‐maintained SERS activity after four cycles. This work demonstrates the superiority of taking advantage of plasmon‐assisted oxynitride semiconductors as a high‐performance SERS platform and provides new opportunities for developing robust visible‐light‐driven recyclable SERS substrates. Abstract : 3D hierarchical gallium oxynitride nanosheets decorated with Ag nanoparticles are demonstrated as robust visible‐light‐driven recyclable substrates for ultrasensitive surface enhanced Raman scattering sensing. The as‐fabricated substrates show a high enhancement factor of 5.2 × 10 7 and an attractive recyclability at visible‐light irradiation, which could be attributed to the surface plasmon resonance and the enhanced charge transfer at the metal/semiconductor interface.